Participation of women in the labormarket in the years 2006–2014. EU ststes clustering - Matuszewska-Janica, Aleksandra (Acta Universitatis Lodziensis. Folia Oeconomica, 2017)
The main aim of the analysis was European Union’s states clustering in point of view of female activity on the labour market. The data was obtained from the Eurosat’s Labour Force Surveys from years 2006–2014. K-means algorithms was the main analysis method. Obtained results indicate to a wide variety of different forms of women’s labour market participation among European Union countries. We can mention three phenomena that have been most highlighted. (1) We found a high percentage of women working in part-time work, especially in the Netherlands. (2) The results show a high proportion of full-time employed women, especially in the EU countries from the former Eastern Bloc. (3) We noted a significant proportion of selfemployed among the employed women in the countries of Southern Europe (Greece, Italy, Portugal, Spain) and in Poland. So, in terms of female economic activity, Poland has a similar pattern as the Southern European countries (also in terms of self-employment).